Du processus de production d’une nouvelle image de la ville de Chefchaouen (Rif occidental) - Khalid Ghailane (Les Cahiers d’EMAM)
The image of the city is a subject that preoccupies researchers, essentially for what it reveals about material and mental representations and insofar as it becomes a “brand image” of a territory. These images interest us because they give rhythm to the socio-spatial evolutions of a given territory and form strata of knowledge specific to each period. Thus, it is possible to reveal the strategic shift made by the actors of Chefchaouen in order to build a specific image, which will become its “official brand” in 2013, with the slogan: “The Blue Pearl”, and to erase the image associated with cannabis cultivation. The shift from a plurality of representations to a single image reflects the desire of the dominant elite to turn the production of this new image of the city into an asset, due to its identity and heritage dimensions, for political and economic interests.